(untitled) (Texas Journal of Medical Science, 2023)
COVID-19 (from the English Coronavirus disease 2019) is a new epidemic infectious disease characterized by a relatively high contagiousness and the likelihood of developing life-threatening complications in the form of acute respiratory distress syndrome, acute respiratory and multiple organ failure. a retrospective analysis of the incidence, clinical course and treatment of children with COVID-19 who were treated in a specialized hospital for the treatment of patients with coronavirus infection. We conducted a retrospective analysis of the case histories of 86 children of various ages who were hospitalized with a confirmed diagnosis of a new coronavirus infection COVID-19 in September-November 2020. There were 51 (%) boys, 34 (%) girls. Depending on age, patients were divided into 4 groups: up to 1 year - 7 (%), from 1 year to 6 years - 27 (%), from 7 to 12 years - 26 (%) and over 12 years - 26 (% ). Studies have shown that children with mild COVID-19 were treated on an outpatient basis and therefore were not included in the surveyed group. Children with moderate and severe forms of COVID-19 received inpatient treatment, and in our study, patients with moderate course - 57 (66.3%), and a severe course was noted in 29 (33.7%) children.